Antifungal, Hydrolytic Enzyme Activity, and Identification of Gut Bacterial in Feces of Black Soldier Fly (Hermetia illucens) Larvae - Maulida, Meirina Nur; Fatmawati, Umi (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
AbstractBlack soldier fly (BSF) (Hermetia illucens) is a type of fly that has larvae called maggots with potential as a waste bioremediation agent. Maggot from BSF has unique digestive characteristics with a diversity of bacteria in it which helps maggot digest organic materials by producing various hydrolytic enzymes. Fecal bacteria in maggots also have potential antifungal activity. This research aimed to identify the hydrolytic and antifungal enzyme activity of maggot fecal bacteria (Hermetia illucencs). Hydrolytic enzyme activity is carried out by measuring the hydrolytic zone in the test medium. The antifungal antagonist test was carried out on Phytophthora sp. using the dual agar culture method. The results of the enzyme activity test showed that isolate MNM 001 had proteolytic enzyme activity, MNM 002 had amylolytic, and proteolytic enzyme activity, and was able to dissolve P elements. MNM 003 had cellulolytic, amylolytic, and proteolytic enzyme activity. From the results of the antagonist test, MNM 001, MNM 002, and MNM 003 have antifungal activity against Phytophthora sp. of the three isolates, isolates MNM 002 and MNM 003 had the best hydrolytic enzyme activity and were identified using the 16S rRNA gene. The results of amplification of the 16S rRNA gene from MNM 002 and MNM 003 indicated that the two isolates were close to the genus Brevibacterium.AbstrakBlack soldier fly (BSF) (Hermetia illucens) adalah jenis lalat yang memiliki larva disebut maggot dengan potensi sebagai agen bioremediasi sampah. Maggot dari BSF memiliki karakterisitik pencernaan unik dengan keragaman bakteri di dalamnya yang membantu maggot mencerna bahan organik dengan menghasilkan beragam enzim hidrolitik. Bakteri pada feses maggot juga memiliki potensi aktivitas antifungi. Tujuan dari penelitian ini adalah untuk mengidentifikasi aktivitas enzim hidrolitik dan antifungi dari bakteri feses maggot (Hermetia illucens). Aktivitas enzim hidrolitik dilakukan dengan mengukur zona hidrolitik pada medium uji. Uji antagonis antifungi dilakukan terhadap Phytophthora sp. dengan metode dual culture agar. Hasil uji aktivitas enzyme menunjukkan isolat MNM 001 memiliki aktivitas enzim proteolitik, MNM 002 memiliki aktivitas enzim amilolitik, proteolitik, dan mampu melarutkan unsur P. MNM 003 memiliki aktivitas enzim selulolitik, amilolitik, dan proteolitik. Hasil uji antagonis MNM 001, MNM 002, dan MNM 003 memiliki aktivitas antifungi terhadap Phytophthora sp. Ketiga isolat tersebut, isolate MNM 001, MNM 002, dan MNM 003 memiliki aktivitas enzim hidrolitik terbaik dan diidentifikasi menggunakan gen 16S rRNA. Hasil amplifikasi gen 16S rRNA dari MNM 002 dan MNM 003 mengindikasikan bahwa kedua isolat tersebut memiliki kedekatan dengan genus Brevibacterium.